Conservation of Soil Moisture Using Mulch of Green Bean Plants (Vigna Radiata) - Frederikus Suburika; Yosefina Mangera; Wahida Wahida (Faculty of Agriculture, Musamus University, 2018)
The aim to this study was to determine the effect of plastic silver mulch and rice straw mulch on soil moisture conservation of green bean so that the plant can grow in dry season with enough water. The method used in this study was a randomized block design with three treatments: no mulch (T0), plastic silver mulch (T1) and rice straw mulch (T2). The parameters observed were physical soil of initial and final research, soil moisture measurements every 3 days, as well as growth and crop production parameters including plant height, number of seeds in pods, 100 seeds weight, sample plant production and total production. The results showed that the physical of soil analyzed were clay textured soil, preliminary porosity 60.77 and at the end of the study increased to 77.50%, organic matter 1.52%, initial bulk density 1.04 g/cm3 at the end of the study decreased to 0.60 g/cm3, soil permeability of 7.77 cm / hour and available water is 13.95%. The use of rice straw mulch from the beginning to the end of the study showed the best water content while the use of plastic silver mulch and no mulch showed water content not much different. The use of palstic silver mulch gives the highest yield of the best crops on 14 HST measurements where the plastic silver mulch differs markedly by the rice straw mulch and no mulch. The yield of green beans produced in the treatment of plastic silver mulch using the best results with a total production of 2.00 tons/ha, this result is significantly different from no mulch but not significantly different of rice straw mulch. Rice straw mulch is better used for soil conservation because it can improve soil aeration, retain water, prevent soil erosion, and increase organic matter on the soil.